On Ipermodernità by Raffaele Donnarumma - Florian Mussgnug (Between, 2014)
Literature investigates, explores and lives reality. It is the place of our intelligibilty. This is the reason why contemporary literature is so important to everybody, regardless its aesthetic value. However, to give reason of the present is a hard and almost impossible work, as stated by Jean-Paul Sartre in his famous 1939 essay about William Faulkner's The Sound and the Fury.